ASUHAN KEBIDANAN KOMPREHENSIF PADA NY. F UMUR 29 TAHUN DI PMB SRI BUDI ASTUTIYARMI AMD.KEB JLEGONG BEJEN TEMANGGUNG - Eni Dwi Rahayu; Sri Rahayu; Sri Mularsih (Lembaga Pengembangan Kinerja Dosen, 2022)
MMR and IMR reflect the health and quality of life of the community. AKI in Temanggung Regency in 2018 was 9 cases or 87.62/100,000 KH. IMR as much as 12.85/1,000 KH. The purpose of the study was to provide comprehensive midwifery care to Mrs. F, aged 29, at the midwife Sri Budi Asturiyarmi Amd. Keb Jlegong, Bejen Temanggung. Comprehensive midwifery care is care that is provided comprehensively from pregnancy, maternity, newborn, postpartum and family planning. Midwifery care is carried out using midwifery management according to Varney which includes assessment, formulating a diagnosis, identifying a diagnosis, planning care, managing care and evaluating. This type of research is a documentation study, the design is qualitative, and is presented in an exploratory descriptive form. The study was conducted in the midwife Sri Budi Asturiyarmi Amd.Keb Jlegong, Bejen Temanggung in May-June 2020. The sample of the study was Mrs. F, aged 29, 39 weeks pregnant. There were no complications in Mrs.F's pregnancy, 9x ANC for Mrs.F, delivery on April 8, 2020. BBL male gender, weight 2750 grams. The placenta is born complete. Postpartum visits 4x. Contraception using 3 MONTHS INJECTING KB. There are some gaps between theory and practice in standard antenatal care 14 T pregnancy (size of TFU, TT immunization and HB test) and in the 1st stage of labor that should be monitored but the patient came with complete opening. Suggestions for health workers are able to provide health services according to standards and be able to improve service quality.